(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The marriage of Ferdinand II, King of Aragon, and Isabella, Queen of Castile, in 1469, did unify the Christian Spain under the same crown. It followed this arrangement that Spain became a super European state strong on land and in the sea. The new monarchy scored, in 1492, great success. Granada, the last Moslem State, in Al Andalusia, fell to the new Monarchy. The same year witnessed the departure of Christopher Columbus sailed in Atlantic sea heading westward to reach India, where sources of trade where in the hands of Moslem merchants crossing Moslem territories towards Europe. With the advent of 16th century, stimulated by strategic and religious motives, the Spaniards started their occupation of Middle Maghreb with the aim to subdue piracy. The disintegration and weakness of the region helped them to materialize their aim.